Bahasa Inggris - Giovani, Evelin; Istiqomah, Nurul; Kaikatui, Frentianich Mentari (Musamus Journal of Language and Literature, 2024)
This research aims to examine the short story "All Hands" by John R. Platt through the lens of Wendy B. Faris's magic realism theory. This study employs a descriptive qualitative method, utilizing Faris's theory of magic realism which is dissected using five characteristics: the irreducible element; the phenomenal world; unsettling doubts; merging realms; and the disruption of time, space, and identity. The results of this analysis reveal that "All Hands" utilizes a setting similar to the real world but incorporates elements that blur the line between reality and fiction, notably the protagonist's daily transformation of hands. This transformation defies natural laws since human hands do not change, yet it is accepted as reality by the characters in the story. Each hand possesses distinct characteristics and identities, symbolizing the diverse nature of human traits.